2018
DOI: 10.4103/0366-6999.245271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endothelial Microparticles Induced by Hypoxia on Migration and Angiogenesis of Human Umbilical Vein Endothelial Cells by Delivering MicroRNA-19b

Abstract: Background:Microparticles (MPs) are small extracellular plasma membrane particles shed by activated and apoptotic cells, which are involved in the development of atherosclerosis. Our previous study found that microRNA (miR)-19b encapsulated within endothelial MPs (EMPs) may contribute to the upregulation of circulating miR-19b in unstable angina patients. Hypoxia is involved in atherosclerosis as a critical pathological stimulus. However, it still remains unclear whether the increase of miR-19b levels in EMPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…described to be anti-angiogenic on HUVEC cells (Liang et al, 2018). SEVs co-incubated with miR-19 were able to inhibit the formation of capillary-like structures in vitro induced by VEGF, whereas miR-19b alone did not (Figure 3F).…”
Section: Proangiogenic Effect Of Mimic Loaded Sevs In Vitromentioning
confidence: 91%
See 1 more Smart Citation
“…described to be anti-angiogenic on HUVEC cells (Liang et al, 2018). SEVs co-incubated with miR-19 were able to inhibit the formation of capillary-like structures in vitro induced by VEGF, whereas miR-19b alone did not (Figure 3F).…”
Section: Proangiogenic Effect Of Mimic Loaded Sevs In Vitromentioning
confidence: 91%
“…Loading efficacy and transfer experiments were validated using the exogenous cel-miR-39 mimic from C. Elegans . We investigate the different effects of the angiomiR-126 (miR-126) ( Tiwari et al, 2018 ) and the angiogenesis inhibitor, miR-19b ( Liang et al, 2018 ) co-incubated with SEVs both in vitro and in vivo . Moreover, the active role of proteins on EV surface on exogenous RNA binding was evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-19b suppresses the expression of the TGFβRI and TGFβRII genes, thus downregulating the fibrogenesis process [ 22 ]. MiR-19b is regulated by the cMyc gene [ 23 ].…”
Section: Role Of Mirnas 19b-3p In Cadmentioning
confidence: 99%
“…In contrast, high amounts of microparticles (2 × 10 5 particles/well, in a 96-well plate) had an inhibitory effect. Liang et al ( 2018 ), showed that hypoxic HUVEC EVs could also inhibit EC migration and angiogenesis probably due to increased levels of miR-19b in these EVs (5 x 10 4 EVs/well, in a 6-well plate were used). The ability of ECs to stimulate angiogenesis may involve the transfer of miR-214 (Balkom et al, 2013 ).…”
Section: Evs In Neovascularisationmentioning
confidence: 99%